TRADISI âBERZANJENâ MASYARAKAT BANYUWANGI KAJIAN RESEPSI SASTRA TERHADAP TEKS ALBARZANJI - Ashari, Hasim (Jurnal Kawistara, 2012)
Indonesia Muslim society. In Banyuwangi, East Java, the text is quite popular. People of Banyuwangi recite the text for several occasions, such as wedding ceremonies, circumcision, childbirths, the celebrations of the Prophetâs birthday, and so forth. Recitation of the text has been a form of art performance. These practices show are a manifestation of the transformation of Arabic and Islamic culture in Banyuwangi, which have contributed signi cantly to culturasl changes in Banyuwangi, East Java.